A new performance review process could fight cultural bias against women at work - RAO, Aliya Hamid (Institutional Knowledge at Singapore Management University, 2017)
A month or so ago, a friend of mine—a postdoctoral fellow at my university—invited me out for lunch, along with a colleague I’d never met. At lunch, my friend introduced me: “Aliya is a postdoc here. She studies unemployment with a focus on gender, so she can tell you about that if you have any questions